Application of The Game Simon Says for Elementary English learning - Pangesti, Nurmalia Dwi; Farida, Zumiatul; Balqis, Fatika Aurellia Anissa (Prosiding University Research Colloquium, 2021)
This study aims to find out how English learning can run well with a more effective learningmodelin accordancewith 2013 curriculum learning.Previous learning only refers to teachers who make learning seem boring and students are not interested in learning, for that teachers are required to make ways to make learning easier. learning is not monotonous and applies the 2013 curriculum with more modern, effective, efficient, and fun learning. Students have different skills and their own characteristics which of course affect learning in the classroom. In this study, it is known that the selection of English learning methods using games can make it easier for students to understand the material presented by the teacher. This learning strategy with games is suitable for encouraging students compared to using the lecture method in general which seems boring and makes students less understanding of the material. Learning with games, teachers must provide clear and concise instructions using demonstrations for students to understand the instructions. Games can help students create a fun atmosphere, relax lessons, motivate and improve students’ writing skills. The selection of games here uses Simon Says which can train students to communicate and be more active in learning English inclass.